Đặc điểm văn bản thuyết minh bảo tàng trong Tiếng Việt và Tiếng Anh về hệ thống chuyển tác - Nguyễn, Thị Quỳnh Hoa (Viện Hàn Lâm Khoa Học Xã Hội Việt Nam, 2021)
This article focuses on an analysis of the transitivity system used in Vietnamese and English Museum texts, basing on the theoretical frameworks suggested by Halliday for English museum texts and by Hoang Van Van for Vietnamese museum texts. The aim of the research is to analyze the use of different types of process, circumstances and lexical density in Vietnamese and English museum texts. The emerging patterns will be summaried to uncover the representation of ideational meanings in two languages, and to establish the similarities and differences in Vietnamese and English museum texts.